Analisis overreaction pasar pada portofolio saham winner dan loser manufaktur syariah di Bursa Efek Indonesia tahun 2017-2021 - Komariah, Siti; Andriyani, Windi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the occurrence of market overreaction in the loser stock group and the winner stock group of Sharia Manufacturing companies listed on the Indonesia Stock Exchange. The purpose of this study is to examine the market overreaction on the winner and loser stocks of Islamic Manufacturing companies. There are 69 companies, there are 26 stocks classified as winners and 43 stocks classified as losers. This study uses abnormal returns as research variables. Abnormal return is the result obtained from the difference between the actual return and the expected return. Tests using statistics used are independent sample t - test, to test the difference between the average abnormal return loser and the average abnormal return winner. Additional testing uses data depicted by graphs. The results of the study based on hypothesis testing showed that there was no statistically significant overreaction in Sharia Manufacturing companies listed on the Indonesia Stock Exchange for 5 research periods in 2017-2021, the research output showed that the abnormal returns of winner stocks were consistently positive compared to abnormal returns of loser stocks which tended to be negative significantly.